Stock return volatility spillovers under foreign exchange market liberalization : case of Jamaica, Trinidad and tobago and the United States - Kim, Sang W. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Examines whether increase in volatility spillovers is observed from a liberalization in the foreign exchange market of a small emerging stock market.